Contribution of Smoking to Pulmonary Tuberculosis Incidence in Bandung, Indonesia - Raspati Cundarani Koesoemadinata; Panji Fortuna Hadisoemarto; Manik Intan Gumilang; Ida Parwati Santoso; Bachti Alisjahbana (Masters Program in Public Health, 2020)
Background: Primary data reporting the contribution of smoking to tuberculosis (TB) incidence in Indonesia are scarce. This study aimed to estimate the effect of smoking on TB incidence and the risk of tuberculosis attribut